Management of Wernicke's encephalopathy in a pregnant woman at 27 weeks gestation complicated by pre-eclampsia: A case report - Amine Bensaid; Marouane Boukroute; Safae Bekkaoui; Hajar Berrichi; Abdelilah Elrhalete; Hamza Mimouni; Younes Oujidi; Houssam Bkiyar; Brahim Housni; Ahmed Mimouni (Radiology Case Reports)
Wernicke's Encephalopathy (WE) is a rare but severe condition primarily caused by thiamine deficiency, often seen in pregnant women who experience severe vomiting, such as in hyperemesis gravidarum. This case report details a 38-year-old woman at 27 weeks of gestation who developed altered consciousness, cerebellar ataxia, and hyperlactatemia following persistent vomiting. Brain MRI demonstrated characteristic bilateral abnormalities consistent with WE. Early recognition and prompt intravenous thiamine administration led to significant clinical improvement. This case emphasizes the importance of maintaining a high level of suspicion and initiating immediate treatment to prevent irreversible neurological damage in pregnant women presenting with severe vomiting and neurological symptoms. A unique feature of this case is the development of Wernicke's encephalopathy secondary to hyperemesis gravidarum, further complicated by severe pre-eclampsia.